Kemampuan Siswa Dalam Memecahkan Masalah Melalui Metode Resitasi dan Diskusi Pada Pelajaran Biologi Kelas XI Di SMA Negeri 6 Maros - Serly Julianda Sari; Hikmah Rusdi; Nurhidayah (CV. Insight Publisher, 2023)
This research aims to improve the ability to solve biological problems through the application of recitation and discussion methods. This research was carried out at SMA Negeri 6 Maros for the 2023/2024 study year. The type of research used by researchers in classroom action research consists of two cycles and each cycle consists of four stages including: planning, implementation, observation, and reflection. The increase in students' ability to solve biological problems can be seen from the increase in the average learning outcomes of students in class XI MIPA 3, the average problem solving ability of students in cycle I was 74.70 and in cycle II it was 84.81 the increase was equal to 10.11 accompanied by increased student learning outcomes. The results of this research indicate that applying the student recitation and discussion method in biology lessons can improve students' biology problem-solving abilities.